Determinan Efektivitas Pengelolaan Dana BOP PAUD Di Banjarsari - Haryanto, Nabillah Carlotta Rhomadhonia; Saharsini, Astuning (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of accountability, transparency, participation and independence on the effectiveness of BOP fund management in PAUD Banjarsari District. This research is quantitative research that uses a population and sample in the form of a BOP management team, namely the school principal and treasurer. The primary data source used in this research is the results of a questionnaire. There are 158 schools in Banjarsari sub-district that have filled out the questionnaire with a total of 316 respondents. This research uses data analysis techniques in the form of data instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that the application of accountability, transparency, participation and independence influences the effectiveness of BOP fund management.